Sharia-Based Tourism Management in Improving Community Income in Teluk Bakau Village, Riau Islands Province - Helianto,; Pakkanna, Mukhaer; Aditya, Mochammad Yana; Widana, Gusti Oka; Amelia, Amie (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2025)
Tourism plays an important role in regional economic growth. Sharia-based tourism is increasingly developing as a tourism model that prioritizes Islamic principles in service and destination management. This concept not only attracts Muslim tourists but also opens up economic opportunities for local communities. Teluk Bakau Village in Gunung Kijang District, Bintan Regency, has great potential in developing sharia-based maritime tourism with supporting natural resources and local wisdom. This study aims to analyze the management of sharia-based tourism in Teluk Bakau Village and its impact on local community income. A qualitative approach with a phenomenological method was used in this study. Data were collected through interviews with tourists and business actors in the tourist area. Data analysis was carried out using the data reduction method to see the relationship between sharia tourism and community income. The results of the study show that sharia-based tourism management has been implemented in several aspects, such as providing facilities in accordance with sharia principles such as Sharia principles in providing facilities include the existence of adequate places of worship, provision of halal food and drinks. However, obstacles are still encountered in promotion and supporting infrastructure. The implications of this research emphasize the importance of government support and cooperation between business actors and the community in developing sustainable sharia tourism that has a positive impact on the local economy.